Access to justice: A literature review on labour courts in Europe and Latin America - Eusebi Colàs-Neila; Estela Yélamos-Bayarri (International Labour Organization (ILO), 2020)
This paper is aimed at offering an overview of the bibliographical discussion on Labour Courts in Europe and Latin America, stating what specific topics academics have shown interest in. The period under review runs from 2000 to the summer of 2019 in order to incorporate the latest reforms and legislative changes in this area. The material scope is limited to procedural aspects of labour courts, including access to the courts (representation), existence of different procedures, resources and instances. For this reason, the structure followed in this report takes into account the logical sequence of the legal institutions that comprise procedural law, offering some proposals to further research in this area.
Keywords: 330; labour relations; labour law; government and public administration; governance